1974
DOI: 10.1677/joe.0.0610355
|View full text |Cite
|
Sign up to set email alerts
|

Corticotrophin-Like Peptides in the Rat Pituitary

Abstract: SUMMARY The pars intermedia of the rat pituitary contains a peptide resembling the 18–39 portion of adrenocorticotrophic hormone (ACTH), which has been termed 'corticotrophin-like intermediate lobe peptide' (CLIP). It can be detected by its cross-reaction with an antiserum directed against the CO2H-terminal portion of the ACTH molecule; it has an amino acid composition identical to the 18–39 portion of human ACTH, except for one less glycine and an extra valine residue, and it is rapidly released from neuroint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0

Year Published

1976
1976
1981
1981

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(46 citation statements)
references
References 13 publications
4
42
0
Order By: Relevance
“…Immunoreactive (midportion antibody) and bioreactive ACTH concentrations of median eminence and medial basal hypothalamus observed in the present study are approximately 1/25th and 1/30th respectively, of those observed by us and others (22) for whole pituitary. Posterior pituitary concentrations of bioreactive ACTH have been reported (22)(23) to be one-fourth of those found in the anterior lobe; most of the ACTH content of the posterior pituitary (which includes both pars intermedia and posterior lobe) is material with COOHterminal-like immunoactivity (COOH-terminal/bioreactive ratio, approximately 100:1) (22). Since the weight of median eminence plus medial basal hypothalamus is about one-third that of the pituitary, the total amount of bioreactive ACTH in this area is roughly 1/100th that in pituitary.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Immunoreactive (midportion antibody) and bioreactive ACTH concentrations of median eminence and medial basal hypothalamus observed in the present study are approximately 1/25th and 1/30th respectively, of those observed by us and others (22) for whole pituitary. Posterior pituitary concentrations of bioreactive ACTH have been reported (22)(23) to be one-fourth of those found in the anterior lobe; most of the ACTH content of the posterior pituitary (which includes both pars intermedia and posterior lobe) is material with COOHterminal-like immunoactivity (COOH-terminal/bioreactive ratio, approximately 100:1) (22). Since the weight of median eminence plus medial basal hypothalamus is about one-third that of the pituitary, the total amount of bioreactive ACTH in this area is roughly 1/100th that in pituitary.…”
Section: Discussionsupporting
confidence: 70%
“…The elution pattern from Sephadex G-50 gel filtration was arbitrarily divided into three sections (to represent activity of the three peaks present: fractions 8-11, 12-16, and [17][18][19][20][21][22] and the percentage of the total immunoreactivity (midportion antibody, this being more representative of biological ACTH § The NH2-terminal antibody reacts almost equally on a molar basis with ACTHI-39, ACTH'24, and a-MSH but not with ACTH17-9, ACTHII-24, or ACTHI-10; the midportion antibody reacts with ACTH1-39 and ACTHII-24 on an equimolar basis, but not with a-MSH, j3-MSH, ACTHI-10, or ACTH17-9. …”
Section: Resultsmentioning
confidence: 99%
“…The immunohistological results, however, are not definitive because of the commonality in amino acid sequences between ACTH and «MSH [Li, 1972;Baker, 1973;Howe, 1973], and between ACTH and the corticotropin-like intermediate lobe peptide [Scott et al, 1974] and lipotropin [Li, 1972]; the latter 2 peptides are also present in the PI [Moon et al, 1973;Dessy et Herlant, 1974;Scott et al, 1974].…”
Section: Discussionmentioning
confidence: 99%
“…Thus the same cell appears to contain a number of peptides including *MSH, ACTH activity, and a corticotrophin-like intermediate lobe peptide (CLIP) [Scott et al, 1974] and perhaps also lipotrophins [Dessy and Herlant. 1974], all with common amino acid sequences.…”
Section: Discussionmentioning
confidence: 99%